Еталонна модель адаптивної системи керування лінійним двигуном - Заблодський, Микола Миколайович; Ковальчук, Станіслав Ігорович (Національний технічний університет "Харківський політехнічний інститут", 2020)
Подано результати математичного моделювання лінійного двигуна на основі чисельних методів, що визначають електромеханічні характеристики двигуна. Знайдено закономірності виникнення гальмівних зусиль при збільшені швидкості руху та розроблено ефективну модель системи адаптивного керування для усунення параметрів невизначеності, пов’язаних з інерційним навантаженням, силою тертя та опором. Досягнуто високої точності та швидкості моделі адаптивного керування лінійним двигуном.

Purpose. Presentation the results of mathematical modelling based on known numerical analysis methods. By writing a model behind the magnetic equivalent circuits method in the MATLAB software environment, the electro-mechanical characteristics of a linear motor and the causes of the occurrence of braking forces with increasing speed were obtained. The Model Reference Adaptive Control (MRAC) for the linear motor was developed in the MATLAB software environment. The model takes into account the influence of the uncertainties parameters of the linear motor due to inertial load, friction, ripple force and electrical parameters. Based on the structure of the motor, the model of MRAC control is utilized to reduce the effect of parametric uncertainties on the motor movement. The developed model achieves high accuracy and speed of adaptive control of a linear motor.
Model Reference Adaptive Control for linear motor
Keywords: математична модель; mathematical model